Compensation and Work Culture on Organizational Performance with in mediation by Work Satisfaction in Fire Department Service of Sungai Penuh City - Syamsudirman, Syamsudirman; Yurmain, Hendra; Heryanto, Heryanto (Archives of Business Research, 2019)
This study aims to examine the effect of compensation and work culture on organizational performance by mediating work satisfaction on Fire Department and Rescue of Sungai Penuh City. This research is motivated by the fact that Compensation, Work Culture and Job Satisfaction influence Organizational Performance. The independent variables in this study are Compensation, Work Culture and Job Satisfaction. The dependent variable in this study is the Organizational Performance of the Fire Department and Rescue of Sungai Penuh City. The data in this study are primary data obtained from questionnaires distributed directly to respondents. Data collected from 162 respondents, which are Operational Staff of the Fire Department and Rescue of Sungai Penuh City. The hypothesis in this study was tested using path analysis. From the results of data analysis using path analysis, it is known that the Compensation (X1) and Work Culture (X2) variables have a positive and significant effect on Job Satisfaction (X3) and Compensation (X1), Work Culture (X2) and Job Satisfaction (X3). Significantly on the organizational performance of the Sungai Penuh City Fire and Rescue Service (Y).The results of this study prove that Compensation, Work Culture and Job Satisfaction affect the Organizational Performance of the Fire Department and Rescue of Sungai Penuh City. The performance of the Sungai Penuh City Fire and Rescue Service will increase if the compensation provided is in accordance with the work performed.